IN EDUCATIONAL OPPORTUNITIES AND CHALLENGES IN THE ERA OF REVOLUTION 4.0 IN IMPROVING THE NATION'S COMPETITIVENESS - Madhakomala, R; Widianti, Sri; Zahra, Siti Elvina (International Journal of Business, Law, and Education, 2022)
The competitiveness of the Indonesian nation in the eyes of the world is still low, this is because the quality of human resources is still low. To overcome the low quality of human resources, a very important role is the world of education. With the advent of the 4.0 revolution era, now is an opportunity as well as a challenge for the world of education to carry out reforms through government policies, curriculum improvements, improving the quality of educators and students' competencies, switching to digital literacy and preparing human resources who have an understanding of cultural values and character. who are solid in facing the world in the 4.0 revolution era. This study uses analysis from relevant journals and textbooks as well as expert views.